Promotion of Tourism and Recreation in the Wilno Region in the 1920s and 1930s - Włodzimierz Gański (Jan Długosz University in Częstochowa, 2024)
The purpose of the work is to study the system of tourism and recreation promotion in the Wilno region in the 1920s and 1930s. To fulfilthe intended purpose of the study, the author used scientific methodology of a historical type. For the first time, the article presents a systematic description of the main methods of tourism and recreation development in the Wilno Region in the 1920s and 1930s, when this region was incorporated into the Second Polish Republic. This study presents the promotion of tourism and recreation in the region through the publication of specialized literature and other printed materials. It shows the contribution of various national and regional organizations, associations and unions to the promotion and development of tourism and recreation in the region. Moreover, the paper comprises an analysis of the promotion of recreation and tourism through promotions and advertising campaigns, as well as through the provision ofdiscounts on railway tickets. In the future, the presented research may provide useful material for further research on the history of the Wilno region and the history of tourism and recreation in Poland, Lithuania and Belarus.